Advanced maternal age as a risk factor of maternal deaths in childbirth - Salazar, Miguel (2015)
OBJECTIVES: To determine the risk for birth and perinatal morbidity and mortality in the elderly mother pregnant. DESIGN: Retrospective clinical study of cross section. MATERIALS AND METHODS: Pregnant Women 35 years or older treated at the San Juan de Dios Hospital in Callao, between January 1990 and December 1991. birth outcomes and maternal and perinatal morbidity and mortality with the pregnant minor is compared 35 treated at the same time. RESULTS: Of 10 445 deliveries, 744 were for añosas pregnant women (7.7%). There were significantly more births añosas dystocic in pregnant women (19.2% vs 10.6%), including breech presentations (7.3%), transverse (0.9%) and other rare (0.6%), having served more vaginal breech births (6.1% vs 2%); the incidence of caesarean sections was 11%. The cesareada previous cesarean was the most common cause in both groups. The maternal mortality rate was 397 per 100 000 live births in most pregnant women and 41 per 100 000 live births in the less than 35 years, unlike statistical significance. In the elderly mother, perinatal mortality was due more often to severe asphyxia (30%), prematurity (16.6%) and congenital malformations (13.3%), the rate of perinatal mortality in aged pregnant was 39, 7 per 1000 live births, and under 35 years 24.8 per 1,000 live births, a statistically significant difference. The overall perinatal mortality rate was 27.8 per 1,000 live births. CONCLUSIONS: The pregnant woman 35 or older has high reproductive risk and requires good preconception counseling, prenatal care with a focus on risk and disposal of fetal malformations, institutionalized childbirth and maternal and perinatal monitoring pre-, intra- and post-partum.